Groundwater–surface water mixing shifts ecological assembly processes and stimulates organic carbon turnover - James C. Stegen (Nature Portfolio, 2016)
Groundwater-surface water mixing zones link critical ecosystem domains, but attendant microbe-biogeochemistry-hydrology interactions are poorly known. Here, the authors show that groundwater-surface water mixing stimulates respiration, alters carbon composition, and shifts the ecology from stochastic to deterministic.